IMPACT OF WASIT POWER PLANT EFFLUENTS ON BIODIVERSITY OF BENTHIC FAUNA IN TIGRIS RIVER, PROVINCE WASIT/ IRAQ - & Meshjel, Jebure (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of environmental study is to investigate the effects of the discharge of Wasit power plant in Al-Zubaidiya city on the physical- chemical factors and biodiversity of benthic invertebrates community of Tigris River, for a period from October 2017 to Augusts 2018. The total number of benthic invertebrates in four stations was 12866 individual. These benthic invertebrates belonged to 8 taxonomic units. This study includes some statistical environmental indexes (Relative abundance index, Shannon-Weiner Diversity Index, Species Uniformity Index, Species Richness Index and Jaccard Index). The results reveal that the environmental indexes were decreased at station 2 and thermal Wasit power plant negatively effects benthic invertebrate community at station 2 near the effluent waste pipe site.